Light‐induced complex formation of bacteriophytochrome RpBphP1 and gene repressor RpPpsR2 probed by SAXS. (12th July 2019) - Papiz, Miroslav Z.; Bellini, Dom; Evans, Kate; Grossmann, J Günter; Fordham‐Skelton, Tony
Abstract : Bacteriophytochrome proteins (BphPs) are molecular light switches that enable organisms to adapt to changing light conditions through the control of gene expression. Canonical type 1 BphPs have histidine kinase output domains, but type 3 Rp BphP1, in the bacterium Rhodopseudomonas palustris (Rps. palustris), has a C terminal PAS9 domain and a two‐helix output sensor (HOS) domain. Type 1 BphPs form head‐to‐head parallel dimers; however, the crystal structure of Rp BphP1ΔHOS, which does not contain the HOS domain, revealed pseudo anti‐parallel dimers. HOS domains are homologs of Dhp dimerization domains in type 1 BphPs. We show, by applying the small angle X‐ray scattering (SAXS) technique on full‐length Rp BphP1, that HOS domains fulfill a similar role in the formation of parallel dimers. On illumination with far‐red light, Rp BphP1 forms a complex with gene repressor Rp PpsR2 through light‐induced structural changes in its HOS domains. An Rp BphP1: Rp PpsR2 complex is formed in the molecular ratio of 2 : 1 such that one Rp BphP1 dimer binds one Rp PpsR2 monomer. Molecular dimers have been modeled with Pfr and Pr SAXS data, suggesting that, in the Pfr state, stable dimeric four α‐helix bundles are formed between HOS domains, rendering Rp BphP1functionally inert. On illumination with light of 760 nm wavelength, four α‐helix bundles formed by HOS dimers are disrupted, rendering helices available for binding with Rp PpsR2. Abstract : The bacteriophytochrome Rp BphP1 forms a complex with repressor Rp PpsR2 when stimulated with far‐red light, causing a host of genes responsible for photosynthesis to be switched on. Photo‐isomerization of biliverdin IXα pigments causes long range structural changes from the far‐red (Pfr) to the red (Pr) absorbing state. These changes disrupt a four α‐helix bundle (magenta), making the HOS domain helix‐turn‐helix motif available for complex formation with Rp PpsR2.